O futebol na cidade de Belo Horizonte: amadorismo e profissionalismo nas décadas de 1930 e 1940 - Sarah Teixeira Soutto Mayor (2017)
This present investigation is aimed to analyse the history of football in the city of Belo Horizonte, Minas Gerais, between the 1930s and 1940s, more accurately from 1933, when professionalism was adopted in the city. We tried to verify how the implementation of this new regime impacted the daily life of the city, by means of the analysis of a time frame still not very well documented in the historical studies of football in the capital of Minas Gerais. The 1940s received a special particular emphasis in this study, taking into account certain peculiar characteristics of that moment, besides the unique structure of the city. As a method, thirty-nine newspapers and magazines edited in the cities of Belo Horizonte, Rio de Janeiro and Buenos Aires (this choice was guided by the dialogues established among the three sport centres), and that were published and circulated at the time were analysed. Minor personal and institutional files were also consulted, as well as memorial reports. The interpretation of the sources were based on the construction of categories of analysis: as amateurism and professionalism; Modernity, tradition, class, culture and civilization, and the idea of sports field and distinction; all linked to the history of the city of Belo Horizonte and its relationship with sports. In summary, we found that intense conflicts and misunderstandings marked the postprofessional period in the capital of Minas Gerais, involving meanings about amateurism and professionalism that coexist on the discursive level that sometimes valued modernity, as well as tradition. Several divisions of power and legitimacy resulted in distinctive sports fields, which after the establishment of professionalism, relegated to amateurism to a peripheral and disqualified place in the citys football hierarchy (which contrasted with the exponential growth of amateur clubs in various locations in Belo Horizonte). Other issues may be listed as conclusive elements. The promises of professionalism, by the time it was implemented, came up against a concrete reality that created new challenges and new demands, such as: structural and financial problems for clubs and the city's own sports structure. The precariousness of the profession and the valorisation of a profitable structure (machine) were factors that, most of all, impacted the players themselves. The problems arising from the continuous departure of the athletes from Minas Gerais (one of the main arguments for the implementation of the regime) had a direct impact on the clubs and the attempts to rival the state to the cities of Rio de Janeiro and São Paulo. Finally, the findings concerning America CF's decision to change the colours of its uniform contributed to a new rereading of the professionalization process in Belo Horizonte, as well as the production of "official histories" and foundational myths, not only in relation to this Club, but in a broader context taking into consideration other Brazilian clubs.